2017
DOI: 10.1097/htr.0000000000000231
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Stroke Among Older Medicare Antidepressant Users With Traumatic Brain Injury

Abstract: Objective To estimate the risk of stroke associated with new antidepressant use among older adults with traumatic brain injury (TBI). Participants 64,214 Medicare beneficiaries aged ≥65 years meeting inclusion criteria and hospitalized with a TBI during 2006 to 2010. Design New user design. Generalized estimating equations were used to estimate the relative risks (RR) of stroke. Main Measures Primary exposure was new antidepressant use following TBI identified through Medicare Part D claims. The primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…183,184 Emerging evidence suggests that initiation of treatment with a selective serotonin reuptake inhibitor (SSRI) among older adults hospitalized for TBI was associated with increased risk of hemorrhagic, but not ischemic, stroke. 185 This finding was further supported by a recent population-based study that identified an association between SSRI initiation and spontaneous hemorrhagic stroke among patients taking oral anticoagulants. 186 Further research is needed to determine the mechanism of post-TBI stroke and SSRI-associated hemorrhage in order to inform safe management of post-TBI depression (which is common and undertreated in older adults 187 ) as well as optimal post-TBI stroke prevention strategies.…”
Section: Mortalitymentioning
confidence: 66%
“…183,184 Emerging evidence suggests that initiation of treatment with a selective serotonin reuptake inhibitor (SSRI) among older adults hospitalized for TBI was associated with increased risk of hemorrhagic, but not ischemic, stroke. 185 This finding was further supported by a recent population-based study that identified an association between SSRI initiation and spontaneous hemorrhagic stroke among patients taking oral anticoagulants. 186 Further research is needed to determine the mechanism of post-TBI stroke and SSRI-associated hemorrhage in order to inform safe management of post-TBI depression (which is common and undertreated in older adults 187 ) as well as optimal post-TBI stroke prevention strategies.…”
Section: Mortalitymentioning
confidence: 66%
“…Selective serotonin reuptake inhibitors (SSRIs) are frequently used to treat depression and other psychiatric disorders and have been suspected of increasing the risk of bleeds through mechanisms affecting platelet function . Several studies of SSRI use as a risk factor for severe bleeds have been published, including studies of intracranial hemorrhage . However, in most studies, different intracranial bleed events have been pooled, a practice criticized by some, as it may conceal effects particular to one type of bleed .…”
Section: Introductionmentioning
confidence: 99%
“…This approach has previously been used in pharmacoepidemiology studies using Medicare claims data. 17,18 PDC was calculated by dividing the number of days’ supply a statin was available during a month by the number of days in a month (30). Since beneficiaries had six months of coverage prior to TBI, pre-TBI statin use was divided into four categories: 1) use in the first or second month immediately prior to TBI; 2) use that was three or four months prior to TBI; 3) use that was over four months prior to TBI; and 4) no use prior to TBI.…”
Section: Methodsmentioning
confidence: 99%
“…Statin use was lagged one month for TBI sequelae outcomes to ensure the exposure preceded the outcome. 18,24 Statin use was not lagged for the mortality models because observation time for beneficiaries ends at death; therefore, mortality will always follow the exposure. This is not necessarily true for beneficiaries who experience TBI sequelae events because beneficiaries are censored following the month an event is experienced.…”
Section: Methodsmentioning
confidence: 99%